Reduction in SARS-CoV-2 Oral Viral Load with Prophylactic Mouth Rinse - Ghasemi, Shohreh; Nadji, Seyed Alireza; Heidari, Ali; James, Jeffrey N.; Karimi-Galougahi, Mahboobeh; Raygani, Negar; Khazaei, Salman; Mehri, Freshteh; Poormohammadi, Ali; Bashirian, Saeid; Mehrpooya, Maryam; Miresmaeili, Amirfarhang; Jalilian, Farid Azizi; Shirahmadi, Samaneh; Keramat, Fariba; Soltanian, Alireza; Ansari, Nastaran; Zeynalzadeh, Farhad; Ebrahimi, Amirali; Dashti, Amirreza; Bloomquist, Ryan F.; Dashti, Mahmood (European Journal of General Dentistry, 2022)
Objectives The medical and health facilities are at high risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. This study tested the preprocedural prophylactic mouthwash rinses to reduce the oral viral load. The findings from this study will help the practitioners to select the best mouthwash for the patients to mitigate the risk of transmission during aerosolizing. This study aimed to evaluate the effectiveness of four commonly used types of mouthwash in reducing intraoral viral load among hospitalized coronavirus disease 2019 patients.Materials and Methods This prospective cohort study was conducted with 116 patients referred to the Masih Daneshvari Hospital in Tehran, Hamadan University of Medical Sciences of Hamadan City, and Mashhad University of Medical Sciences. Patients were randomized into four groups with each group rinsed their mouth with 20 mL of 2% povidone-iodine, 1% hydrogen peroxide, normal saline as a control study group, or 0.12% chlorhexidine, respectively, for 20 seconds. The standard reverse transcription polymerase chain reaction method evaluated the virus load before and at 1 hour, 2 hours, and 4 hours after using the mentioned mouthwash.Results Our results revealed that chlorhexidine and H2O2 showed the highest efficiency in reducing SARS-Co-2 load in the oral cavity and nasopharyngeal region of patients; they increased the Ct values by 9 to 10 (before: 25.84 vs. after 32. 4, p < 0.455) (17.333 vs. after 26.497, p <0.097).Conclusion Our findings suggest that chlorhexidine and H2O2 could be used in dental clinics to reduce the risk of transmitting the SARS-CoV-2 virus from infected individuals to dentists before dental procedures.
Keywords: mouthwashes; viral load; COVID-19; chlorhexidine; povidone-iodine; hydrogen peroxide